Management of Finger Painting Learning in Fostering and Developing Fine Motor Stimulation in Children Aged 2-4 Years in the Jungle School Nature Play Group - Marta, Grasalwa Dhifaf Virlia; Shofwan, Imam (Universitas Negeri Semarang, 2025)
Finger painting is one of the effective sensory-motor stimulation methods in developing fine motor skills in early childhood. This study aims to evaluate the effectiveness of finger painting activities in developing fine motor skills of children aged 2-4 years, with a focus on KB Alam Jungle School in Gunung Pati District, Semarang City. The method used is descriptive qualitative research, with primary and secondary data collection through interviews, observations, and documentation. The validity of the data was obtained through triangulation techniques. The results of the study stated that finger painting activities were effective in stimulating the development of fine motor skills in children aged 2–4 years. With good planning, flexible implementation, and a supportive environment, children can explore and improve hand-eye coordination, as well as develop creativity and confidence. The role of teachers as facilitators is important to create positive interaction and learning comfort. Evaluation is carried out qualitatively through observation and portfolio, allowing teachers to design sustainable learning strategies. This approach also supports the child's overall social and emotional development.